Impact of malnutrition on early outcomes after cancer surgery: an international, multicentre, prospective cohort study. Issue 3 (March 2023) - ,; Riad, Aya; Knight, Stephen R; Ghosh, Dhruv; Kingsley, Pamela A; Lapitan, Marie Carmela; Parreno-Sacdalan, Marie Dione; Sundar, Sudha; Qureshi, Ahmad Uzair; Valparaiso, Apple P; Pius, Riinu; Shaw, Catherine A; et al.
Summary: Background: Malnutrition represents a key priority for global health policy, yet the impact of nutritional state on cancer surgery worldwide remains poorly described. We aimed to analyse the effect of malnutrition on early postoperative outcomes following elective surgery for colorectal or gastric cancer. Methods: We did an international, multicentre, prospective cohort study of patients undergoing elective surgery for colorectal or gastric cancer between April 1, 2018, and Jan 31, 2019. Patients were excluded if the primary pathology was benign, they presented with cancer recurrence, or if they underwent emergency surgery (within 72 h of hospital admission). Malnutrition was defined with the Global Leadership Initiative on Malnutrition criteria. The primary outcome was death or a major complication within 30 days of surgery. Multilevel logistic regression and a three-way mediation analysis were done to establish the relationship between country income group, nutritional status, and 30-day postoperative outcomes. Findings: This study included 5709 patients (4593 with colorectal cancer and 1116 with gastric cancer) from 381 hospitals in 75 countries. The mean age was 64·8 years (SD 13·5) and 2432 (42·6%) patients were female . Severe malnutrition was present in 1899 (33·3%) of 5709 patients, with a disproportionate burden in upper-middle-income countries (504 [44·4%] of 1135) and low-income and lower-middle-income countries (601 [62·5%] of 962). After adjustment for patient and hospital risk factors, severe malnutrition was associated with an increased risk of 30-day mortality across all country income groups (high income: adjusted odds ratio [aOR] 1·96 [95% CI 1·14–3·37], p=0·015; upper-middle income: 3·05 [1·45–6·42], p=0·003; low income and lower-middle income: 11·57 [5·87–22·80], p<0·0001). Severe malnutrition mediated an estimated 32% of early deaths in low-income and lower-middle-income countries (aOR 1·41 [95% CI 1·22–1·64]) and an estimated 40% of early deaths in upper-middle-income countries (1·18 [1·08–1·30]). Interpretation: Severe malnutrition is common in patients undergoing surgery for gastrointestinal cancers and is a risk factor for 30-day mortality following elective surgery for colorectal or gastric cancer. There is an urgent need to examine whether perioperative nutritional interventions can improve early outcomes following gastrointestinal cancer surgery worldwide. Funding: National Institute for Health Research Global Health Research Unit.